Current Advances in Red Blood Cell Generation Using Stem Cells from Diverse Sources - Yoojin Seo; Kyung-Hwa Shin; Hyung Hoi Kim; Hyung-Sik Kim (Stem Cells International)
Blood transfusions hold an indispensable part in the modern healthcare system. Up to date, the blood supply is largely dependent on donations. Unfortunately, collecting the clinical-grade blood products has become a challenging mission due to accelerated population aging, which not only increases the need for blood transfusions but also decreases the number of healthy donors. Moreover, individuals with severe hematological abnormalities or rare blood phenotypes need alternative therapeutic approaches instead of conventional blood transfusion. In these aspects, the concept of in vitro/ex vivo production of blood cells has been emerging and many attempts have been focused on manufacturing mature erythrocytes, so-called red blood cells (RBCs), the most common and important component among the blood derivatives. In this review, we provide a general overview regarding the current strategies for generating RBCs from various stem cell sources including pluripotent stem cells (PSCs) as well as circulating blood stem cells and the remaining challenges that must be overcome prior to their practical application.